1965
DOI: 10.2337/diab.14.11.700
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Diabetic Retinopathy: II. Retinopathy and Nephropathy in Spontaneous Canine Diabetes

Abstract: Retinal and renal observations on dogs with spontaneous diabetes mellitus are presented. Retinal vessels were prepared by the trypsin digestion, flat retinal technic and examined by light microscopy. Kidneys were examined by light and electron microscopy. Nondiabetic dogs of comparable ages served as controls. Retinal vessels in some diabetic subjects showed mural pericyte degeneration with “ghost” formation and zones of focal acellularity surrounded by aneurysms or hypercellular capillary shunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
2

Year Published

1966
1966
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
3
17
1
2
Order By: Relevance
“…Prevalence of retinopathy in humans with diabetes in the United States was recently reported as 28.5%, with a strong correlation with duration of diabetes 28. Previous studies describing retinopathy in dogs with naturally occurring diabetes have reported similar prevalence values as this study, ranging from 3 to 21% 5, 7, 29, 30. Although hypertension is also a well‐known risk factor for development and progression of diabetic retinopathy in humans,28, 31 a similar correlation was not found in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Prevalence of retinopathy in humans with diabetes in the United States was recently reported as 28.5%, with a strong correlation with duration of diabetes 28. Previous studies describing retinopathy in dogs with naturally occurring diabetes have reported similar prevalence values as this study, ranging from 3 to 21% 5, 7, 29, 30. Although hypertension is also a well‐known risk factor for development and progression of diabetic retinopathy in humans,28, 31 a similar correlation was not found in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Various manifestations, such as microaneurysm formation, capillary pericyte loss and capillary basement membrane thickening, have been consistently reported in humans with diabetes [13,14] and some diabetic animal models [3,6,15,16]. OLETF rats had similar capillary changes.…”
Section: Discussionmentioning
confidence: 54%
“…Sibay (1967) sugeriu que a diabetes precisa estar presente por pelo menos cinco anos no cão, antes da manifestação da retinopatia. Existem vários casos reportados de retinopatia em cães com diabetes melito espontânea (Patz 1962,1965, Sibay 1967, Monti 1976, Barnett 1981, Ono 1986). Recentemente, em 2003, Landrey realizou estudo retrospectivo, em que avaliou 52 cães diabéticos e 179 cães não diabéticos submetidos à cirurgia de catarata.…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified